2019
DOI: 10.1186/s12883-019-1460-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary diffuse meningeal melanomatosis – a rare form of meningeal melanoma: case report

Abstract: BackgroundMeningeal melanomatosis is a rare type of central nervous system neoplasm (with incidence ranging between 3 and 5%) that develops in the course of malignant melanoma. In a small percentage of cases, meningeal melanomatosis may develop without a primary focus. It affects the leptomeninx. The clinical activity of the disease is uncharacteristic, with a number of neurological symptoms developing over weeks or months.Case presentationA 45-year-old male patient presented with consciousness disturbance, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…In some human cases, as well as in our case, malignant melanocytes were observed in the CSF [3,9,15]. Although the probability of detecting malignant melanocytes in the CSF remains unclear in human literature, repeating CSF tap may be beneficial, since the first tap could only reveal elevated protein and pleocytosis without neoplastic cells, even when lesions were found on MRI [3,9]. In a case series, two out of three patients had malignant melanocytes in the CSF, but in one of them, neoplastic cells were only detected from the repeated CSF tap [3].…”
supporting
confidence: 68%
See 2 more Smart Citations
“…In some human cases, as well as in our case, malignant melanocytes were observed in the CSF [3,9,15]. Although the probability of detecting malignant melanocytes in the CSF remains unclear in human literature, repeating CSF tap may be beneficial, since the first tap could only reveal elevated protein and pleocytosis without neoplastic cells, even when lesions were found on MRI [3,9]. In a case series, two out of three patients had malignant melanocytes in the CSF, but in one of them, neoplastic cells were only detected from the repeated CSF tap [3].…”
supporting
confidence: 68%
“…Although diagnosis of primary CNS melanomas without biopsy is challenging, aggressive subarachnoid space invasion in meningeal melanomatosis may raise the odds of the presence of malignant cells in the CSF. In some human cases, as well as in our case, malignant melanocytes were observed in the CSF [ 3 , 9 , 15 ]. Although the probability of detecting malignant melanocytes in the CSF remains unclear in human literature, repeating CSF tap may be beneficial, since the first tap could only reveal elevated protein and pleocytosis without neoplastic cells, even when lesions were found on MRI [ 3 , 9 ].…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…In our case, two months after the first symptoms, the patient died. The patient had a history of drug addiction, presenting psychomotor agitation and aggressive behavior, as can be observed in many cerebral neoplasms [ 54 , 55 , 56 , 57 ]. Morais described a case of delirium in a patient with brain melanoma metastases [ 58 ] and other authors reported headache and diplopia in a 27-year-old man affected by primary meningeal melanocytoma in the anterior cranial fossa [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) classification divides the melanocytic lesions of the central nervous system into three types: diffuse melanosis, meningeal melanocytoma (benign course), and melanoma [ 210 ]. Considering the latter, two forms of PIMM should be highlighted: solid tumors and diffuse meningeal melanomatosis [ 211 ].…”
Section: Unusual or Unknown Primary Site Melanomasmentioning
confidence: 99%